Potencial da Gliciridia em consorciação com Capim marandu em substituição a adubação nitrogenada - Araujo, Helber Rodrigues de (2014)
The experiment was conducted to evaluate the availability of forage and weight gain in grazing Marandu Grass (Brachiaria brizantha (Hochst. ex. A. Rich.) Webster cv. Marandu) fertilized with nitrogen in the absence and presence of Gliricidia (Gliricidia sepium (Jacq ) Kunth , Walp), conducted in the Experimental Jorge Prado Sobral , belonging to Embrapa Tabuleiros Costeiros, in Nossa Senhora das Dores - SE, during the rainy season (May to October) and of water restrictions, dry period (November to April) in the years 2008 to 2011. The treatments had consisted of four doses of nitrogen (0, 80, 160 and 240 kg/ha.year) applied in grass pastures Marandu and consortium use Gliricidia with Marandu Grass (0 kg/ha.year of N), wrapped in an experimental design of randomized blocks with six repetitions. The Marandu pastures were grazed in intermittent stocking system, in Rotary, grazing with seven days of occupation and 35 days of rest in the rainy season and seven days of occupation and 49 days of rest in the dry period. During the rainy season and drought treatments composted with nitrogen provide increased availability of total dry matter, leaf, culm in effect positive in stocking rate, individual weight gain and weight gain per area of cattle. It was noted also that in the rainy season there was an increase in the percentage of leaf and culm, reducing the percentage of dead material and increasing crude protein of leaf and culm. While in the dry season it was noted an increase in the availability of biomass of dead material effect this hydric deficit arising from the period. In the rainy season between the Consortium marandu grass and Gliricidia showed similar or higher efficiency the largest doses of nitrogen to increase the percentage of leaf, crude protein and weight gain per area of cattle. While in the dry season the consortium between grass Marandu and Gliricidia showed similar or higher efficiency the largest doses of nitrogen to increase the availability of individual sheet, weight gain, and stocking rate weight gain per area of cattle.